HUBUNGAN WAKTU TUNGGU DENGAN TINGKAT KEPUASAN PASIEN DALAM MENDAPATKAN PELAYANAN KESEHATAN DI POLI UMUM PUSKESMAS PRACIMANTORO I - Febri Rahma Wati; Prita Devy Igiany; Yul Asriati (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
One of the efforts in the health sector is the creation of quality service. Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares with what he expects. The purpose of the study was to determine the relationship between waiting time and the level of patient satisfaction in obtaining health service at the public polyclinic of Pracimantoro I Health Care. Design the study used a quantitative analysis design with a cross-sectional approach and the data collection using a questionnaire. The method used in the analysis is the customer satisfaction indeks (CSI) method. The population in this study was patients who came for treatment at the Pracimantoro I Health Center in 2021 with a total of 16.511 people. The sampling method used an accidental sampling technique which was taken by 60 respondents. The result of the analysis of patient satisfaction using CSI with the result of 77.123 which means that the level of patient satisfaction in the general poly Pracimantoro I Health Center is in the satisfied category. Of the 60 respondent, more than half stated that the waiting time st the general polyclinic was not long (93,3%) and from the result of the kolmogrov-smirnov statistical test there was a relationship between waiting time.